Analisis Komparasi Etika Islam Ibnu Miskawaih dan Modifikasi Perilaku dalam Psikologi Barat: A Comparative Analysis of Ibn Miskawaihâ€™s Islamic Ethics and Behavior Modification in Western Psychology - Hanifah, Nor; Soleh, Achmad Khudori; Bastomi, Riza (Tasfiyah: Jurnal Pemikiran Islam, 2025)
This study aims to compare the concept of moral development according to Ibn Miskawaih with behavior modification in Western psychology. This topic is intriguing due to the similarities and differences between the two that can be scientifically explained. The research uses a qualitative method with a library research approach. The findings indicates that Ibn Miskawaih's moral development or ethics is based on the Al-Qurâ€™an and philosophy, focusing on the soulâ€™s drive to engage in good behavior without considering specific benefits, in order to achieve life perfection and happiness. According to him, the ethical hierarchy consists of al-khaiyrÂ (goodness), al-saâ€˜Ädah (happiness), and al-faá¸Ä«lahÂ (virtue). In Ibn Miskawaihâ€™s view, character formation is a potential for noble morality that can be achieved through the principle of the middle path (al-wasaá¹), influenced by internal factors such as the soul and external factors such as the environment. Meanwhile, behavior modification in Western psychology is based on theories by Western scholars that emphasize observable behavior resulting from stimulus-response and aim to shape planned behavior through learning and reinforcement processes. The comparison between the two reveals differences in basic thinking, characteristics, factors influencing behavior change, and goals. However, there are similarities in the strategies used to shape character, namely through training, habituation, reinforcement, and modeling roles within the environment.Â